2010
DOI: 10.1007/s00415-010-5597-1
|View full text |Cite
|
Sign up to set email alerts
|

Theta burst stimulation over the primary motor cortex does not induce cortical plasticity in Parkinson’s disease

Abstract: The purpose of this study was to investigate whether a period of continuous theta burst stimulation (cTBS) induces cortical plasticity and thus improves bradykinesia of the upper limb in Parkinson's disease. In eight patients with Parkinson's disease (two females; mean age: 68.5 ± 5 years; disease duration: 4 ± 3 years) electrophysiological (motor evoked potentials, contralateral and ipsilateral silent period) and behavioural (Purdue pegboard test, UPDRS motor subscore) parameters were evaluated before (baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 30 publications
7
39
0
Order By: Relevance
“…Interestingly, the first dose of l -DOPA failed to modulate the plasticity in these patients and there was no significant difference between the more and less affected sides. Deficient iTBS induced LTP-like plasticity in PD was observed in other studies (58, 60, 61). In one study (60) following facilitatory iTBS, neither the medication state (ON and OFF), disease severity nor the presence of LID had any effect on this lack of potentiation, suggesting that the reduced M1 plasticity in PD is unrelated to dopaminergic therapy, disease severity, and the developments of LID.…”
Section: M1 Plasticity Studies In Pdsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the first dose of l -DOPA failed to modulate the plasticity in these patients and there was no significant difference between the more and less affected sides. Deficient iTBS induced LTP-like plasticity in PD was observed in other studies (58, 60, 61). In one study (60) following facilitatory iTBS, neither the medication state (ON and OFF), disease severity nor the presence of LID had any effect on this lack of potentiation, suggesting that the reduced M1 plasticity in PD is unrelated to dopaminergic therapy, disease severity, and the developments of LID.…”
Section: M1 Plasticity Studies In Pdsupporting
confidence: 83%
“…Similarly, instead of potentiation, iTBS produced no change in excitability in eight patients ON dopaminergic drugs (61). In another study (58), inhibitory cTBS on M1 did not change in M1 excitability in PD patients. Another study (64) demonstrated altered plasticity in both early and late stages of PD and different effects of dopaminergic medications at different stages of the disease.…”
Section: M1 Plasticity Studies In Pdmentioning
confidence: 86%
“…Similarly to what observed with PAS, TBS protocols failed to induce plasticity in patients with PD in most studies (12, 13). Suppa et al (13) tested the effects of intermittent theta-burst stimulation (iTBS), a technique used to induce LTP-like plasticity in M1, in patients with PD, OFF and ON dopaminergic therapy, with and without l -DOPA -induced dyskinesias (LIDs).…”
Section: Tbs Protocolsupporting
confidence: 58%
“…Our sample size is within the range of other TBS publications in Parkinson's disease (Eggers et al, 2010;Huang et al, 2011b) and Dystonia (Huang et al, 2010), but our findings need to be confirmed in larger samples. In this context, one should note that despite the observed differences in plasticity responses between both groups, larger sample sizes are needed to explain the exact directions and the underlying mechanisms.…”
Section: Limitationsmentioning
confidence: 42%